2021
DOI: 10.3390/ijerph181910001
|View full text |Cite
|
Sign up to set email alerts
|

Does the Direct Settlement Policy of Trans-Provincial Outpatient Expenses Aggravate the Siphoning Effect? An Empirical Study on Yangtze River Delta, China

Abstract: To solve the problem of reimbursing trans-regional medical expenses, using only cross-regional manual reimbursement but not direct medical insurance card settlement, China implemented a pilot policy of direct settlement of trans-provincial outpatient expenses (DSTOE) in the Yangtze River Delta region. Due to the differences in inter-regional medical development, patients often migrate from areas with low-level medical resources to the high-level areas, a phenomenon that we define as the “siphoning” of trans-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The insured with poor PCBMI have the following four characteristics: First, we found that those with a lack of recent basic medical insurance use experience had an obvious negative tendency to evaluate the convenience of BMIS. The possible explanation for this finding is that the public’s awareness of the improved policy reform is insufficient, especially in the medical service areas they do not frequently use [ 26 ]. Those who lack experience might precipitate the difficulty of obtaining medical service and inconvenient basic medical insurance in the past into the collective memory [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insured with poor PCBMI have the following four characteristics: First, we found that those with a lack of recent basic medical insurance use experience had an obvious negative tendency to evaluate the convenience of BMIS. The possible explanation for this finding is that the public’s awareness of the improved policy reform is insufficient, especially in the medical service areas they do not frequently use [ 26 ]. Those who lack experience might precipitate the difficulty of obtaining medical service and inconvenient basic medical insurance in the past into the collective memory [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many researchers showed that “medical expense burden” was associated with the convenience of basic medical insurance reimbursement [ 25 ]. Ma et al and Li et al proposed that “health status” and the “policy information awareness” of the insured were the important aspects affecting their assessments of the convenience of BMIS [ 6 , 26 ]. Further, Sanogo et al viewed “insured experience” as fundamental for the insured to evaluate the convenience of BMIS services [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the results of the chi square test showed that the insured who lacked recent basic medical insurance use experience had lower PBBMI. The public's perceptions of reform and change are lagging, especially in areas where they do not enter frequently ( 22 ). The insured who had not used medical care recently were more likely to be affected by the collective memory of the once extremely insufficient medical security in Heilongjiang ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the insured's perceptions of the benefits of the basic medical insurance system (PBBMI), most scholars have explored the system design problems of the current BMIS via quantitative research methods, such as the poor protection effect of medical insurance on the seriously ill population ( 20 ), the insufficient protection on the fairness of different groups ( 21 ), the poor publicity effect of medical insurance information ( 22 ), and the poor portability of medical insurance ( 5 ). In most related qualitative studies, scholars have studied BMIS by interviewing system administrators or the insured.…”
Section: Introductionmentioning
confidence: 99%
“…This was in order to form an appropriate medical procedure of primary diagnosis, two-way referral, linkage between different ranks of medical institutions, and division of emergency and non-urgent treatment. 5 Unfortunately, many proposed reform measures have not been actioned as yet ( 18 ). Without clear results from the policy changes made in the pilot, it is difficult to implement a hierarchical medical system on a large scale.…”
Section: Literature Reviewmentioning
confidence: 99%